A review of experimental approaches to fracture toughness evaluation at the micro-scale. (5th July 2019) - Ast, J.; Ghidelli, M.; Durst, K.; Göken, M.; Sebastiani, M.; Korsunsky, A.M.
Abstract: The discipline of fracture mechanics was born almost a century ago through the pioneering work of A.A. Griffith, and saw particularly rapid growth in the second half of 20th century when it became an indispensable tool in the development of advanced transportation, civil construction, and energy systems. Forty years ago, Materials & Design published a series of papers devoted to the state-of-the-art in the field of Fracture Mechanics. The present review reflects the lasting legacy and surviving importance of this theme: it is associated with the Virtual Special Issue on nanoscale materials testing and characterisation, and focuses on the modern experimental approaches to fine scale fracture toughness evaluation, with particular emphasis on micro-cantilever bending and micro-pillar splitting. The fundamental aspects of these approaches are overviewed, and their application to a range of systems is described. Implications for further development of these methods are discussed. Graphical abstract: Unlabelled Image Highlights: Review of toughness evaluation at the micro- to nano-scale Fundamentals and applications of micro-pillar splitting testing Fundamentals and applications of micro-cantilever testing Overview of achievements, challenges and opportunities